Frans Florschütz as founding father of pollen analysis in the Netherlands, and expansion of palynology into the tropics. Issue 4 (4th July 2022) - Hooghiemstra, Henry; Richards, Keith
Abstract: Frans Florschütz (1887‒1965) developed pollen analysis in the Netherlands as a biostratigraphical tool on the interface between geology, palaeobotany, soil science and climate history. He was involved in agricultural practice and the building of large infrastructure. Florschütz established centres of pollen analysis at the universities in Wageningen (1924) and Utrecht (1928), was appointed professor in Leiden (1948) and after retirement founded a chair in pollen analysis in Nijmegen (1960). The botanical institute in Utrecht was Florschütz' alma mater where he supervised students over two decades. Since 1947 Florschütz trained micropalaeontologists how to use fossil pollen as a biostratigraphical tool in oil industry. He inspired Jonker in Utrecht and Zagwijn in Leiden. Several of his students focused on tropical areas and used applied and academic pollen analysis to explore tropical ecosystems, such as Polak (1930s) and Muller (1950s) in southeast Asia, Van Zinderen Bakker (1950s) in southern Africa, Van der Hammen (1950s) in northern South America, Van Zeist and Bottema (1960s) in the Middle East. He stimulated Shell to be a pioneer in using pollen-based stratigraphy in oil exploration in the tropics. In the late 1940s and 1950s biostratigraphers Germeraad, Hopping, Kuyl, Muller and Waterbolk studied samples from the Caribbean, Nigeria and British Borneo in Shell's Pollen Laboratories in Maracaibo (Venezuela) and in The Hague. In 1944 'pollen analysis' was renamed 'palynology' for good reasons. Laboratory practice in applied research developed differently from academic palynology leading to a hybrid research field. Implications are briefly discussed.